Electric vehicles as electricity storages in electric power systems - Popović, Vlado (Logistics and sustainable transport, 2018)
Improvements in battery technology make electric vehicles more and more suitable for the use as electricity storages. Many benefits could be achieved by using electric vehicles for storing electricity in their batteries. This paper talks about the idea of electric vehicles as electricity storages in electric power systems. The idea has a great number of supporters, but also a significant part of the professional community believes that is unfeasible. This paper is not classified in either side and strives to give a realistic picture of this idea. For this purpose, findings from papers published in scientific journals are mainly used. There is also some information from websites, mainly for some technical issues. Partly, the opinions of the authors are present. Specificities of EVs and EPSs that enabled the birth of this idea are explained along with proposed concepts through which the idea can be implemented. Keeping with the vehicle to grid concept, issues about the implementation of the idea are considered. Achievements in the practical realization of the idea are also presented.
Keywords: electric vehicles; electricity; storages; V2G